Interfacial evaporation for solar still applications using low-cost nano-graphite wick - Muapper Alhadri; Shaher Alshammari; Abdulhamid F. Alshammari; Awwad Alshammari; Mohamed M.Z. Ahmed; Ahmed Farag; Mohamed Elashmawy (Case Studies in Thermal Engineering, 2025)
This study developed low-cost nano-graphite-textural wick for the interfacial evaporation process. The nano-graphite was mixed with black dye and saturated a white cotton wick. A simple glass cup was used as condenser. The glass cup has simple geometry that can be easily utilized for any number in array form according to required demand. Moreover, readymade (waste) or specially manufactured glass cups from recycled glass materials can be used with very competitive low-cost water production systems. The saline water inside the wicked cup is absorbed in the wick texture and spreads in a larger exposed interfacial surface area. Results showed superior performance of the developed system with productivity and efficiency enhancement of 30.9 % and 31.4 %, respectively, reaching 5.235 L/m2day freshwater yield and 42.7 % daily efficiency. Moreover, the developed system was able to produce freshwater with a very competitive cost of 9.9 $/m3 compared with other techniques in literature ranging from 15 to 25 $/m3 in most cases. This cost can be further enhanced for developed large-scale projects. Large projects enable mass production of recycled materials and other device components with lower operation and maintenance costs with higher thermal efficiency due to using arrays of cups with less heat losses expectation.